Market-Making Practices of Private Tutoring in Finland: Commercialization of Exam Preparation for Admission to Higher Education - Suvi Jokila; Nina Haltia; Sonja Kosunen (Sage Publications Ltd., 2022)
Purpose: This study focuses on courses that prepare applicants for universities’ highly competitive
entrance examinations in Finland. The analysis clarifies the market-making practices and the
construction of this field.
Design/Approach/Methods: To understand these processes, we use C¸ alis¸kan and Callon’s five
framings for studying marketization as a heuristic framework. In our analysis, we combine different
data sets, including data on course provision, thematic interviews, documents, and ethnographic
notes.
Findings: In this article, we argue that the preparatory course markets in Finland are an example
of private tutoring which operates in the privacy of the university applicants’ exam preparation
process, thus commercializing this process. The market making of this type of private tutoring is an
assemblage of a variety of agents that interact in parallel with each other.
Originality/Value: This study aims to contribute to the systemic understanding of the assemblage
of private tutoring markets in an equality-focused Nordic country by providing new heuristic
lenses from economic sociology through which to view private tutoring.